The care of Filipino juvenile offenders in residential facilities evaluated using the risk-need-responsivity model. (July 2016) - Spruit, Anouk; Wissink, Inge B.; Stams, Geert Jan J.M.
Abstract: According to the risk-need-responsivity model of offender, assessment and rehabilitation treatment should target specific factors that are related to re-offending. This study evaluates the residential care of Filipino juvenile offenders using the risk-need-responsivity model. Risk analyses and criminogenic needs assessments (parenting style, aggression, relationships with peers, empathy, and moral reasoning) have been conducted using data of 55 juvenile offenders in four residential facilities. The psychological care has been assessed using a checklist. Statistical analyses showed that juvenile offenders had a high risk of re-offending, high aggression, difficulties in making pro-social friends, and a delayed socio-moral development. The psychological programs in the residential facilities were evaluated to be poor. The availability of the psychological care in the facilities fitted poorly with the characteristics of the juvenile offenders and did not comply with the risk-need-responsivity model. Implications for research and practice are discussed.